Pengaruh Pemberian Bokashi Kotoran Ternak terhadap Pertumbuhan dan Hasil Tanaman Kacang Edamame (Glycine max (L) Merril) - Pratama, Idham Maysar; Heiriyani, Tuti; Gazali, Akhmad (Agroekotek View, 2025)
Edamame is a pIant that is often used as a heaIth food, because the edamame plant has nutritional content that is quite good for body health. Therefore increasing edamame soybean production is very important. Bokashi is a fertilizer made from organic materials, which is made by fermenting organic materials using EM-4 technoIogy. Bokashi is used as an organic fertilizer to enrich the soiI and not damage the environment. This research aims to determine the effect of giving bokashi and the best dose between bokashi treatments on the growth and production of edamame bean pIants. This research was prepared using the Randomized BIock Design (RAK) method with six repetitions. The experiment consisted of four treatment levels of bokashi fertilizer doses with one control treatment, namely d0 : 350 kg.ha-1 Mutiara NPK fertilizer (42 grams/plot) d1 : 2.5 ton.ha-1 bokashi fertilizer (300 grams/plot) d2 : 5 ton.ha-1 bokashi fertilizer (600 grams/plot). d3: 7.5 ton.ha-1 bokashi fertilizer (900 grams/plot). The results of the research showed that giving bokashi had no real effect on the growth and production of edamame bean plants and the best dose of giving bokashi on the growth and production of edamame bean plants was 2.5 tons ha-1